Juridical Implications of Judges Decisions with Incorrect Legal Considerations (Analysis of Decision Number: 802/Pdt.G/2019/Pa.Pwt) - Avilya, Dhyni; Nurul Hidayah, Astika (LPPM Universitas Harapan Bangsa, 2024)
The Court's judgment is necessary. The Court must examine, resolve, and decide the case filed by the Court. However, there were court errors in the decision. This study aims to determine and analyze the law on the Judge's wrong legal consideration in the Ratio Decidendi theory and the juridical implications of the Judge's decision that misapplied the law in decision Number 2802/Pdt.G/2019/Pa.Pwt. The method used in this research is normative juridical, where the law is conceptualized as what is written in the legislation. The data source in this research uses secondary data. The data collection method in this research uses literature study, namely by collecting literature such as books, scientific journals, and primary legal materials to support this research, as well as identification and clarification of legal facts in the field by asking questions to sources that are by this research. Based on the results of the study and discussion of the legal analysis of the Judge's decision, which is wrong in its legal considerations in the Ratio Decidendi theory, namely the reasons that determine the decision formulated in the verdict. This part of the consideration cannot be separated from the verdict and has a legally binding force, which can be formulated as a legal rule. The legal impact of an incorrect decision in its legal considerations does not affect the ruling but is binding on the parties, provided that it is not appealed or cancelled.